Comparative studies of photophysical and photochemical properties of solketal substituted platinum(II) and zinc(II) phthalocyanine sets - Zorlu, Yunus; Dumoulin, Fabienne; Durmuş, Mahmut; Ahsen, Vefa (Pergamon-Elsevier Science Ltd, 2010)
A complete set of platinum(II) solketal substituted phthalocyanines has been synthesized and characterized. To evaluate their potential as Type II photosensitizers for photodynamic therapy, comparative studies of their photophysical and photochemical properties with analogous zinc(II) series have been achieved: electronic absorption, fluorescence quantum yields, lifetimes, and fluorescence quenching by benzoquinone, as well as singlet oxygen generation and photodegradation. It appears that platinum(II) phthalocyanines are worth being used as Type II photosensitizers, as they exhibit good singlet oxygen generation and appropriate photodegradation. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Platinum; Zinc; Photosensitizer; Quantum yields; Singlet oxygen generation; Photodegradation